The brown fat-secreted adipokine neuregulin 4 is decreased in human and murine chronic kidney disease. Issue 2 (August 2019) - Kralisch, Susan; Hoffmann, Annett; Klöting, Nora; Frille, Armin; Kuhn, Hartmut; Nowicki, Marcin; Paeschke, Sabine; Bachmann, Anette; Blüher, Matthias; Zhang, Ming-Zhi; Harris, Raymond C; Stumvoll, Michael; et al.
Abstract : Objective: Neuregulin 4 (NRG4) has recently been introduced as a novel brown adipose tissue (BAT)-secreted adipokine with beneficial metabolic effects in mice. However, regulation of Nrg4 in end-stage kidney disease (ESKD) and type 2 diabetes mellitus (T2DM) has not been elucidated, so far. Design/methods: Serum NRG4 levels were quantified by ELISA in 60 subjects with ESKD on chronic hemodialysis as compared to 60 subjects with an estimated glomerular filtration rate >50 mL/min/1.73 m 2 in a cross-sectional cohort. Within both groups, about half of the patients had a T2DM. Furthermore, mRNA expression of Nrg4 was determined in two mouse models of diabetic kidney disease (DKD) as compared to two different groups of non-diabetic control mice. Moreover, mRNA expression of Nrg4 was investigated in cultured, differentiated mouse brown and white adipocytes, as well as hepatocytes, after treatment with the uremic toxin indoxyl sulfate. Results: Median serum NRG4 was significantly lower in patients with ESKD compared to controls and the adipokine was independently associated with a beneficial renal, glucose and lipid profile. In mice with DKD, Nrg4 mRNA expression was decreased in all adipose tissue depots compared to control mice. The uremic toxin indoxyl sulfate did not significantly alter Nrg4 mRNA expression in adipocytes and hepatocytes, in vitro . Conclusions: Circulating NRG4 is independently associated with a preserved renal function and mRNA expression of -Nrg4 is reduced in adipose tissue depots of mice with DKD. The BAT-secreted adipokine is further associated with a beneficial glucose and lipid profile supporting NRG4 as potential treatment target in metabolic and renal disease states.